A critical overview of the current myofascial pain literature – July 2015. Issue 3 (July 2015) - Dommerholt, Jan; Hooks, Todd; Grieve, Rob; Layton, Michelle
Summary The current overview includes thirty articles published in the recent past about myofascial pain, trigger points (TrPs) and related topics. In the Basic Research section, several interesting new studies are reviewed addressing the presence of TrPs in patients with low back pain, episodic migraine, or following a meniscectomy. An animal study of the impact of laser fluency opens the door to future studies regarding optimal dosage of low-level laser therapy in the treatment of individuals with TrPs. Six papers focus on TrP dry needling (DN), two on manual therapies, and two on injection therapy. On of the injection papers discusses the occurrence of a cardiac tamponade, which is a very rare potential complication of invasive needling therapies that can easily be avoided with proper needling techniques. Several review studies and other clinical studies conclude this overview.